Imaging of the Pediatric Temporal Bone Abnormalities - Gencturk, Mehmet; Tore, H. G.; Nascene, D. R.; Truwit, C. L. (Journal of Pediatric Neuroradiology, 2016)
Abnormalities of the temporal bone in children may be associated with important morbidity. Congenital, undiagnosed hearing loss occurring can impair normal cognitive development and should therefore be diagnosed and treated as soon as possible. The most common indication of temporal bone imaging in childhood is congenital hearing loss. Both high-resolution computed tomography and magnetic resonance imaging are helpful in diagnosis of a variety of congenital, inflammatory, traumatic, and neoplastic disorder.
Keywords: temporal bone; pediatric; congenital